Caracterização física e química e potencial de deriva de caldas contendo surfatantes em pulverizações agrícolas - Oliveira, Rone Batista de [UNESP]; Antuniassi, Ulisses Rocha [UNESP] (EIA Energy in Agriculture, 2012)
The aim of this work was to evaluate the effect of the addition of different surfactants in physical and chemical properties of spray solutions, droplets spectra and drift potential on agricultural spraying. The surfactants and concentrations (v v-1) were: Haiten (0.1%), Antideriva and Intec (0.05% and 0.1%). The following characteristics were analyzed: surface tension, viscosity, density and electric conductivity. The droplet size spectrum was determined by a laser particle analyzer (Mastersizer S®, version 2.15) including measurements of volume medium diameter (VMD), the percent of droplets below 50 and 100 μm (V50 e V100) and index span. In order to estimate the drift potential, a series of wind tunnel tests were performed with a Teejet XR 8003 flat fan nozzle at 200 kPa (medium droplets) used to apply the spray solutions containing water, the adjuvants and a food color dye (Brilliant blue FD & C no 1) at 0,6% m v-1. The drift was collected on nylon strips transversally fixed along the tunnel at different distances from the nozzle and different high from the bottom part of the tunnel. Drift deposits were evaluated by spectrophotometry. The results showed that the addition of adjuvants changed physical and chemical properties of spray solutions in different magnitudes according to the surfactant. Surfactants changed the droplet spectrum and drift potential, indicating that higher VMD and smaller V100 induced higher percentage of drift.

O objetivo deste trabalho foi avaliar o efeito da adição de surfatantes nas propriedades físicas e químicas, no espectro de gotas e no potencial de deriva em caldas de pulverizações agrícolas. Os surfatantes comerciais utilizados e suas respectivas concentrações foram: Haiten (0,1% v v-1) e Antideriva e Intec (0,05% e 0,1% v v-1). Analisaram-se as propriedades físicas e químicas das soluções tais como a tensão superficial, viscosidade, densidade e condutividade elétrica. O espectro de gotas foi determinado de forma direta em analisador de tamanho de partículas por difração de raios laser, onde foi avaliado o diâmetro mediano volumétrico (DMV), o percentual de gotas menores que 50 e 100 μm (V50 e V100) e a amplitude relativa (AR). Para a avaliação do potencial de deriva realizou-se ensaios em túnel de vento com uma ponta Teejet XR 8003 VK na pressão de 200 kPa (gotas médias), aplicando caldas contendo corante Azul Brilhante (0,6% m v-1) em mistura com os surfatantes. A deriva foi coletada por meio de fios de polietileno posicionados transversalmente ao fluxo de ar a diferentes distâncias da ponta e alturas do piso do túnel. A solução de lavagem de cada fio foi processada por meio de espectrofotometria para quantificação dos depósitos. Os resultados mostraram que a adição de surfatantes alterou as propriedades físicas e químicas das soluções aquosas em diferentes magnitudes, dependendo do surfatante. Os surfatantes modificaram o espectro de gotas e o potencial de deriva, indicando que quanto maior o DMV e menor o V100, menores foram os percentuais de deriva.
Physical and chemical characterization and drift potential of spray solutions with surfactants on agricultural spraying
Keywords: Adjuvants; Droplets size; Wind tunnel; Correlation; Adjuvantes; Tamanho de gotas; Túnel de vento; Correlação